Educating the B40 group of societies towards a sustainable environment: A case study on Rukun Tetangga Jelapang’s achievement - Ng , Richard; Thinakaran Sarangabanly; Pandian Sarangabanly (2019)
This paper presents the findings made on a research carried out in Jelapang Tambahan, Ipoh, Perak. There are 220 households, mostly from B40 category families, and was identified as one of the dengue-prone villages in the Kinta District. A total of 4,812 dengue cases were detected at end of November 2014 with 13 fatalities, of which some of the fatal cases came from this village. The villagers were ignorant of the importance of keeping the environment clean. Twelve (12) illegal dumpsites were detected in this village prior to the start of this research. An action committee was formed which comprised representatives from Rukun Tetangga Jelapang, the Solid Waste Management Corporation and Ipoh City Watch, with the role of educating the Jelapang Tambahan folks through a series of campaigns and recycling projects. Using Ajzen and Fishbein (1980)’s Theory of Planned Behaviour Model as a guiding factor and Kolb (1984)’s Experiential Learning Theory, the education project via Trash-to-Cash sustainable recycling was launched on 4 April 2015. A collection centre within the community was established where participants were requested to turn in their recyclables twice a month in exchange for cash. Recyclables collected were segregated, weighed and recorded every month from April 205 to November 2016. Contributors were paid cash in exchange for the recyclables brought to the centre. The data collected were then tabulated and analysed to establish the trend. Results obtained showed that a total of 8,900 kg of recyclables have been collected giving the participants a supplementary income of RM3,850. The 12 illegal dumpsites prior to the start of the project have disappeared, fatal dengue cases had dropped drastically, and the recycling rate was 13.1% which is higher than the national rate of 10% in 2016. Thus, the outcome of this study can help create an impact to the society by changing their behaviour if the right approach is used to educate them. (Abstract by authors)